1991
DOI: 10.1080/00071669108417336
|View full text |Cite
|
Sign up to set email alerts
|

Limiting amino acids in low protein maize‐soyabean meal diets fed to broiler chicks from 3 to 7 weeks of age

Abstract: 1. An experiment with separately housed male and female broiler chicks was carried out during the period of 3 to 7 weeks of age to determine the limiting amino acids (AA) in a low protein maize-soyabean meal diet. Chicks were fed on diets containing 170, 180, 190 and 200 g crude protein (CP)/kg with or without combined additions of L-threonine (Thr), L-tryptophan (Trp) and L-arginine (Arg) to those in the 180, 190 or 200 g CP/kg diets and a 170 g CP/kg diet with or without combined additions of Thr, Trp, Arg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 2 publications
1
13
0
3
Order By: Relevance
“…Based on the results of a previous experiment (Holsheimer and Janssen, 1991), in which the requirements for limiting amino acids in low protein maize-soyabean meal diets for broilers between 3 and 7 weeks were evaluated, a second experiment was carried out (Schutte et al, 1992). In that experiment it was found that, when low protein maize-soyabean meal diets with sufficient ly:;ine and sulphur-containing amino acids were fed to broiler chicks from 0 to 28 d of age, threonine, arginine and valine were the first, second and third limiting amino acids when the dietary crude protein (CP) content was decreased from 200 to 160 g/kg.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of a previous experiment (Holsheimer and Janssen, 1991), in which the requirements for limiting amino acids in low protein maize-soyabean meal diets for broilers between 3 and 7 weeks were evaluated, a second experiment was carried out (Schutte et al, 1992). In that experiment it was found that, when low protein maize-soyabean meal diets with sufficient ly:;ine and sulphur-containing amino acids were fed to broiler chicks from 0 to 28 d of age, threonine, arginine and valine were the first, second and third limiting amino acids when the dietary crude protein (CP) content was decreased from 200 to 160 g/kg.…”
Section: Introductionmentioning
confidence: 99%
“…Menores valores para conversão alimentar têm sido observados à medida que os níveis de proteína da dieta são aumentados (Holsheimer & Janssen, 1991;Parr & Summers, 1991;Ziggers, 2002). Stringhini (1998) verificou que os valores de 22 a 24% de proteína na fase pré-inicial proporcionaram melhores desempenhos de frangos de corte, o que sugere maior necessidade de proteína neste período.…”
unclassified
“…Invariably, dietary CP will decrease below advocated concentrations when supplemental EAA are not constrained during least-cost formulation. A reduction in CP does not decrease live weight as much as it adversely affects feed conversion and abdominal fat (Mendonca and Jensen, 1989;Holsheimer and Janssen, 1991;Jensen, 1991;Surisdiarto and Farrell, 1991).…”
Section: Introductionmentioning
confidence: 99%